Re-coding the na(rra)tive : disrupting the colonial lens in search of my Maaori self : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Tini, Matt (Massey University, 2022)
The history of Maaori with the Western gaze is complex, and it is in complexity that my practice sits. I begin this exegesis introducing the influence of the colonial lens on Tangata Whenua identities and my lens-based practice, discussing the limiting essentialist paradigms of identity that have generated and maintained colonial stereotypes and notions of authenticity. I then discuss through my moving image work where do we come from | what are we | where are we going (after gauguin) (2022) how simulation can be used as a means to critique and re-code signifiers, or 'signs', of authentic Indigenous identities. This is supported through an analysis of artists and creatives whose use of the lens has demonstrated how colonial tools and narratives can be reclaimed and reworked to suit Indigenous peoples. Within this whakapapa, I emphasize the assertion of cultural and political agency, and advocate for multiplicity as a departure from limiting essentialist notions of authenticity. Reflecting on a notable shift toward ambiguity in my practice, I explore how my photographic body of work the sitters (2022) intersects with Trickster consciousness, blurring binaries of gender, culture, time, and space, stepping further into liminality as a mode for expression of a more diverse Maaori identity. I conclude by considering how Indigenous Futurisms can make available new ways for contemporary Indigenous identities to be imagined and expressed outside colonial impositions. This exegesis is an extensive enquiry of the development of my lens-based practice over the years 2021-2022, suggesting further areas of development and exploration.
Keywords: 360604 Photography, video and lens-based practice